2007
DOI: 10.2165/00019053-200725110-00006
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Entecavir versus Lamivudine with Adefovir Salvage in HBeAg-Positive Chronic Hepatitis B

Abstract: Our analysis suggests entecavir improves health outcomes in a cost-effective manner compared with lamivudine with adefovir salvage or combination therapy, and highlights the importance of using evidence-based effectiveness estimates in economic studies of CHB therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 40 publications
0
48
0
2
Order By: Relevance
“…Several cost-effectiveness studies of first line and salvage therapies particular to other countries have appeared (Kanwal et al 2005, Veenstra et al 2007. A systematic review by Sun et al (2007) covers 14 studies in a range of countries, the authors concluding that -the cost-effectiveness frontiers of treatment alternatives vary and are influenced by the comparators and socioeconomic conditions of countries‖ (p.1369).…”
Section: Drug Treatmentmentioning
confidence: 99%
“…Several cost-effectiveness studies of first line and salvage therapies particular to other countries have appeared (Kanwal et al 2005, Veenstra et al 2007. A systematic review by Sun et al (2007) covers 14 studies in a range of countries, the authors concluding that -the cost-effectiveness frontiers of treatment alternatives vary and are influenced by the comparators and socioeconomic conditions of countries‖ (p.1369).…”
Section: Drug Treatmentmentioning
confidence: 99%
“…Two of the factors involved in the superior efficacy of ETV are its capacity to maintain viral load at undetectable levels and minimal rates of resistance for long periods of time. Some cost-effectiveness studies have been published recently, showing that ETV is a cost-effective alternative in patients with CHB [19][20][21].…”
Section: Treatments Compared Etv Lvd Incrementalmentioning
confidence: 99%
“…Recently, some studies with excellent evidence have been performed which compared these drugs as follows: LAM vs. ADV (4-6), LAM vs. ETV (7,8), LAM vs. LdT (9)(10)(11), ADV vs. ETV (12)(13)(14), ADV vs. LdT (15), ADV vs. TDF (16,17). In a study performed by Heathcote et al, it was reported that TDF and ETV are the two most potent oral antiviral agents for HBeAg-positive patients in the first year of treatment for CHB (18).…”
Section: Introductionmentioning
confidence: 99%